How China Embraces Globalization: From Economic Reform to Global Outreach - Amaliyah, Ridha (The Sunan Ampel Review of Political and Social Sciences, 2024)
China's status as a world economic and political power affects the structure of relations in the Asia region and the global economy. Understanding China's responses to the globalized economy and its current position is a crucial intellectual exercise that offers insights into alternative economic development and governance models. China is an example of a country that has successfully developed utilizing the momentum of globalization, which many scholars overlook. This paper aims to describe China’s political-economic relations in response to globalization. A literature review method is utilized through various academic sources. This paper finds that China's tremendous productive modalities have been a significant factor in the country's march to global economic dominance. China’s accession to the WTO and sustained economic reform and restructuring efforts in the domestic political economy sphere induced a convergence towards internationally accepted financial and market interaction standards. Development milestones ranged from the sources and destination of foreign investments, export-led manufacturing, and BRI projects to green economy policies. China introduced three brand-new initiatives as a strong impetus for advancing humanity’s modernization process and building a community with a shared future for mankind.